PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN GUNUNGSINDUR KABUPATEN BOGOR - Septia Wulandari; Sam Cay (Al Hasanah Barokah Foundation, 2025)
This study aims to determine the effect of competence and work motivation on employee performance at the Gunungsindur District Office, Bogor Regency, both partially and simultaneously. The research method used is quantitative with an associative approach. The population used in this study consists of all non-civil servant employees at the Gunungsindur District Office, Bogor Regency, with a total sample of 32 people obtained through a saturated sampling technique. The data collection techniques used include primary data such as observation, interviews, and questionnaires, as well as secondary data through documentation and literature study. The data analysis techniques used include descriptive analysis, data instrument testing, classical assumption testing, quantitative analysis, and hypothesis testing. The results of the study show that partially, there is a significant effect of competence on employee performance at the Gunungsindur District Office, Bogor Regency, with a t-value > t-table (14.875 > 2.042), and a p-value (sig.) < α (0.000 < 0.05). Partially, there is a significant effect of work motivation on employee performance at the Gunungsindur District Office, Bogor Regency, with a t-value > t-table (14.973 > 2.042), and a p-value (sig.) < α (0.000 < 0.05). Simultaneously, there is a significant effect of competence and work motivation on employee performance at the Gunungsindur District Office, Bogor Regency, with an F-value > F-table (180.158 > 3.33), and a p-value (sig.) < α (0.000 < 0.05).